1D Building Blocks‐Intermingled Heteronanomats as a Platform Architecture For High‐Performance Ultrahigh‐Capacity Lithium‐Ion Battery Cathodes. Issue 2 (28th October 2015) - Kim, Ju‐Myung; Park, Chang‐Hoon; Wu, Qinglin; Lee, Sang‐Young
Abstract : The cathode active particles‐embedded polyacrylonitrile nanofibers/multiwalled carbon nanotubes heteronanomat cathode (HM cathode) is demonstrated as an effective and versatile electrode platform to address the long‐standing challenges of conventional cathodes. The material/structure uniqueness of the HM cathode enables substantial improvements in rate capability, cycling performance and, most notably, areal capacity far beyond those accessible with conventional cathode technologies.